Enterovirus D68 and acute flaccid myelitis—evaluating the evidence for causality. Issue 8 (August 2018) - Messacar, Kevin; Asturias, Edwin J; Hixon, Alison M; Van Leer-Buter, Coretta; Niesters, Hubert G M; Tyler, Kenneth L; Abzug, Mark J; Dominguez, Samuel R
Summary: Increased circulation of enterovirus D68 in 2014 and 2016 temporally and geographically coincided with increases in cases of acute flaccid myelitis, an uncommon condition of paralysis due to lesions in the anterior horn of the spinal cord. The identification of enterovirus D68 in respiratory specimens from cases of acute flaccid myelitis worldwide further supports an association, yet the absence of direct virus isolation from affected tissues, infrequent detection in cerebrospinal fluid, and the absence, until recently, of an animal model has left the causal nature of the relationship unproven. In this Personal View we evaluate epidemiological and biological evidence linking enterovirus D68 and acute flaccid myelitis. We applied the Bradford Hill criteria to investigate the evidence for a causal relationship and highlight the importance of comprehensive surveillance and research to further characterise the role of enterovirus D68 in acute flaccid myelitis and pursue effective therapies and prevention strategies.